Void pattern fluctuation in p-AgBr interactions at 400 GeV/c (JOURNAL OF ADVANCES IN PHYSICS, 2016)
The event-by-event fluctuation of hadronic patterns is investigated by finding a measure of the non-hadronic regions, the voids, for the experimental data of p-AgBr interactions at 400 GeV/c considering the anisotropy of phase space. Two moments of the event-to-event fluctuation of voids, and Sq have been calculated as defined by R. C. Hwa and Q. H. Zhang to quantify the dependence of the voids on the bin sizes. The results suggest that no quark-hadron phase transition of second order have taken place for p-AgBr interactions at 400 GeV/c. The result have been compared with the result of VENUS generated data.